Hashimoto Thyroiditis-Diffuse Vs Nodular? A Case Study In A Rural Tertiary Care Hospital - Harikrishnan, Volga; V, Sudha; Alphonsa, Janice; Srinivasan, Chitra (Annals of Pathology and Laboratory Medicine, 2018)
Background:Hashimoto thyroiditis is an autoimmune disease caused by production of autoantibodies against thyroglobulin and thyroid peroxidase enzyme. Prevalence is 2% in general population and incidence is seven times more in females between 30-50 years of age. It may present as euthyroid, hypothyroid or hyperthyroid state.There is an increased frequency of Hashimoto's thyroiditis (HT) and HT associated thyroid cancer. HT can be presented as diffuse or nodular lesion. The aim of this study is mainly to find out the incidence of diffuse and nodular lesions in HT in patients who came for FNAC for thyroid enlargement. Methods: Retrospective analysis of Hashimoto thyroiditis cases diagnosed by FNAC over the period of six months in Department of Pathology. Review of the clinical records of patients for further clinical, biochemical and radiological details to find out incidence of diffuse and nodular HT. Result: In this study there is increased incidence of HT.Both types (Diffuse and nodular) were present. Mostly occur at the age group of 20 to 50 years and commonly seen in females. Diffuse type had all type of hormonal status (Hyper/Hypo/Euthyroidism) but all the cases of nodular type had only hypothyroid status. Clinical presentation of nodular lesions confirmed with sonographic findings. Conclusion: The rate of occurrence of nodular lesion in Hashimoto thyroiditis with hypothyroidism is high among females aged 20-40 years when compared to diffuse lesions. DOI:10.21276/APALM.1755